The Influence of Double Date Digital Campaign and Electronic Word of Mouth on Erigo Product Purchases on Shopee" Survey of Business Administration Students at International Women's University - Vira Citra Lestari; Ucu Supriatna (Escalate : Economics and Business Journal, 2026)
The development of e-commerce in Indonesia has led to increasingly fierce competition, particularly in the local fashion industry, which utilizes digital platforms such as Shopee. Momentum-based promotional strategies, such as the Double Date Digital Campaign, and marketing communication through Electronic Word of Mouth (e-WOM) are important factors in influencing consumer purchasing decisions, especially among the younger generation. This study aims to analyze the influence of the Double Date Digital Campaign and Electronic Word of Mouth on the purchase decision of Erigo products on Shopee. The research method used is a quantitative approach with a survey technique using a Likert scale questionnaire. The research sample consisted of 95 active student respondents selected using simple random sampling. The data were analyzed using classical assumption tests, multiple linear regression, determination coefficients, and hypothesis testing with the help of SPSS. The results showed that the Double Date Digital Campaign had a positive and significant effect on purchasing decisions, as did Electronic Word of Mouth. Simultaneously, both variables had a significant effect on purchasing decisions with an Adjusted R Square value of 0.678, meaning that 67.8% of the variation in purchasing decisions could be explained by the research model. In conclusion, digital campaign strategies on twin dates were the most dominant factor in driving purchasing decisions, reinforced by the role of online reviews and recommendations in building consumer trust.